Lance nematode pathogenicity on Pterocarpus santalinus seedlings - Sivaprakash, M.; Balasubramanian, P.; Rathakrlshnan, P. (Indian Journal of Agroforestry, 2020)
To assess the pathogenicity of lance nematode, Hoplolaimus seinhorsti on Pterocarpus santalinus, a nursery experiment was conducted in glass house at Fe & RI, Mettupalayam. Polythene bags 25 x 15cm were filled with steam sterilized fine river sand & red earth in the ratio of 3:1. The freshly collected red sanders seeds were pretreated and sown for germination. Fifteen days after germination, the root zone were inoculated with adults and juvenile of H.Â seinhorstiwith the population of 0, 100,200,400 and 600 larvae bag-1. Observation after 120 DAI showed the reduction of 4.6,22.6,31.9 and 52.7% in root length, 24.6,40.5,50.9 and 66.0% in plant weight due to inoculation with 100,200,400 and 600 larvae, respectively when compared to un-inoculated control. The multiplication rate of H. seinhorstiwas 9.3 to 100 larvae kg-1 soil. There was no significant difference in chlorophyll contents due to 600 larvae kg-1 soil (13.2) while the net photosynthetic rate was Significantly reduced, for the larval population more than 200 kg-1 soil.